ANALYSIS OF INVESTMENT ACTIVITIES AS A PREREQUISITE FOR THE EFFECTIVE DEVELOPMENT OF AGRICULTURAL FORMATIONS - STAVNICHUK, VITALII (Herald of Khmelnytskyi National University. Economic sciences, 2021)
The article examines the factors and methods of strengthening investment activity in the agricultural sector of Ukraine. In the broadest sense, investments provide the necessary mechanisms for financing, growth and development of the country’s economy. The analysis shows that in all developed countries the agricultural sector of the economy is supported by the state, as it directly affects the country’s food security and its role and place in the world economy. It was determined that the limitation of state finances, the lack of an effective mechanism for crediting agriculture, a strict and imperfect tax policy, and an increase in the import of agricultural products contributed to the fact that domestic agricultural formations eliminated almost all sources of capital formation and accumulation, which negatively affected the functioning of agrarian and technologically related industries. The author singles out a number of factors that limit the investment attractiveness of the agricultural industry, including: high indebtedness of agricultural enterprises, low innovative activity and the use of outdated technologies, ineffective organization and the use of ineffective approaches to managing the activities of agricultural enterprises and the development of the industry as a whole. Institutional transformations and reforms are necessary, which will be aimed at: firstly, at changing the industry structure due to increasing the technological level of agro-industrial production; secondly, to change the role of the state in the processes of functioning and development of the industry (gradual rejection of protectionism in favor of competition). As a result of the analysis of the dynamics of capital investments in agriculture, it was found that the amount of invested funds increases every year, but their growth rates have significantly decreased, especially in the agricultural sector in recent years. The slowdown in investment volumes is due to many macroeconomic and political factors, the deterioration of the country’s general investment climate, which was the result of the negative impact of a number of reasons, therefore, to solve this problem, ways to intensify investment activity in the industry have been proposed.